The relationships between structural and psychological empowerment and job satisfaction among nurses - Tahere Bonyad Karizme; Tayebe Rahimi Pordanjani; Ali Mohamadzadeh Ebrahimi (حیات, 2016)
Background & Aim: Job satisfaction is of the most fundamental components of mental health in every profession and one of the most important factors in career success. Therefore, identifying factors affecting job satisfaction is necessary. One of these factors is employee empowerment. This study aimed to determine the relationship between structural and psychological empowerment and job satisfaction among nurses.